Upacara Slametan Gua Sam Poo Kong di Semarang dalam Perspektif Multikultural - M. Ikhsan Tanggok (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2005)
The slametan ceremony commonly practiced by the abangan Javanese not only occurs within the Javanese community in Java, but also within the Chinese or Tionghoa community practicing religions other than Islam in Java. The slametan ceremony held to rebuild the Sam Poo Kong cave at the Sam Poo Kong temple in Semarang in 2002 was not just a sacred ritual, but also served as a platform to bring together and unite two different ethnic groups to establish order in society. The approach used in this paper refers to Clifford Geertz’s perspective, which views slametan as an effort or ceremony performed to ward off someone or a group of people from the disturbance of spirits. Additionally, Marcel Mauss’s theory of gift exchange or reciprocity is also employed. According to Mauss’s theory of exchange, no human action is without reciprocity, as all actions expect some form of return, including offerings made to spirits and deities.